The Effect of Price Mix on Purchasing Decisions At PT. Srikandi Diamond Motors Sumedang - Alyusyak, Muhammad Rizki; Kurniawan, Ryan Feryana; Nur'arif, Muhammad Irfan (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
The automotive industry in Indonesia is one of the main sectors that significantly contributes to the national economy. According to data from the Indonesian Automotive Industry Association (Gaikindo), in 2021, a total of 532,756 passenger vehicles were sold, indicating a 7.5% increase compared to the previous year. This study aims to determine the extent of the influence of price mix on purchasing decisions at PT. Srikandi Diamond Motors Sumedang. This research employs a quantitative approach with Simple Random Sampling technique, involving a sample size of 95 respondents. The research findings indicate that the independent variable (Price Mix) has a significant impact on the dependent variable (Purchase Decision). The t-test results reveal that the calculated t- value is -4.797, while the tabulated t-value is 1.66105. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. Meanwhile, the coefficient of determination (R square) is 20.1%, explaining that the influence of price on purchase decisions is 20.1%, while the remaining 79.9% is influenced by other variables not examined in this study. The research findings also demonstrate that the independent variable (Price Mix) significantly affects the dependent variable (Purchase Decision).